Potential use of satellite observations to detect suspended sediment in delta region: a case study of the Red river delta, Vietnam - Hue Thi Dao; Tung Duc Vu (Vietnam Journal of Science, Technology and Engineering, 2020)
Building an integrated river delta basin and coastal management plan in the context of climate change requires suspended sediments data, which plays an important role and is the key component for understanding the hydrology regime in the delta region. Sediments are responsible for carrying a considerable amount of nutrients and contaminants. Most sediment discharge data is acquired by surveys/ data collection activities or by mathematical modelling. However, these methods are costly, time-consuming, and complex. Therefore, in this study, the authors investigate the potential use of satellite observations (MODIS reflectance) to detect suspended sediment flux in the Red river delta (RRD) of Vietnam. The relationships between discharge (Q), suspended sediment concentration (SSC), and total load (L) collected from the three in-situ stations Son Tay station (ST), Thuong Cat station (TC), and Hanoi station (HN) in the RRD are determined by regression analyses of reflectance data (R) obtained from MODIS bands 1-2 (250-m resolution). The results present a close connection between the monthly average of SSC and R and a good statistical relationship between the monthly average of Q and R in HN. At TC and ST, a lower correlation was found compared to HN because of the cloud cover and the position where data was collection in the river. The coefficient of determination ranged from 0.11 to 0.40 for the R-SSC and R-Q relationships. A method of estimating SSC and L at a single point along the river using data from Q and R was proposed based on the relationship correlation results.